Perception and attitude of library and information professionals towards COVID 19 pandemic and the compulsory lockdown in Nigeria - Idhalama, Ogagaoghene Uzezi (Qualitative and Quantitative Methods in Libraries; 2020: Special issue : COVID-19 and the Libraries : the impact of, 2021)
This article investigated perception and attitude of library and information professional towards COVID 19 and the compulsory lockdown in Nigeria. Some of the objectives adopted for the study are: To determine library and information professionals’ perception of COVID 19 pandemic in Nigeria, find out the attitude of library and information professionals towards COVID 19 pandemic in Nigeria, to determine the type of lockdown preferred by Nigerian library and information professionals in time of COVID 19 pandemic, ascertain the perception of library and information professionals towards the COVID 19 compulsory lockdown and one other. An online survey was developed to get responses from 97 Nigerian library and information professionals. Total enumeration sampling technique was adopted and the following findings were recorded: Majority of the respondents in Nigeria are of the view that COVID 19 has changed the whole world, followed by those that perceived Coronavirus as manmade virus from Wuhan, China, most of the respondents indicated that they try to adhere to all the WHO stipulated preventive measures. This was followed by respondents who indicated that they fight against infodemic and also those that disseminate correct and current information about COVID 19, majority of library and information professionals in Nigeria prefer partial lockdown to full lockdown and others, majority of respondents in Nigeria feel that the current lockdown has brought economic recession and acute hunger in the land and one more.